Model Pengembangan Produk Unggulan Kakao Olahan di Sulawesi Tenggara - Rosmawaty, Rosmawaty; Taufik, Yani (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2019)
This study aims to examine the design of superior product development models for processed cocoa in Southeast Sulawesi. The study was conducted in June 2014 until June 2015. Determination of the sample is a case study at the Tinete Prosperous Justice LEM in Kolaka Timur District, Aere District, Tinete Village. The method of data collection in this study was carried out by library research methods and field surveys. Based on the results of the study, it can be concluded that the results of the analysis indicate that the key criteria in selecting superior processed cocoa products are products that are economically capable of providing greater commodity value, availability of skilled human resources in the village, market guarantee for products, availability of raw materials and easy access to technology.